Protocol of the HISTOTHERM study: assessing the response to hyperthermia and hypofractionated radiotherapy in recurrent breast cancer - Thomsen, Andreas R.; Sahlmann, Jörg; Bronsert, Peter; Schilling, Oliver; Poensgen, Felicia; May, Annette M.; Timme-Bronsert, Sylvia; Grosu, Anca-Ligia; Vaupel, Peter; Gebbers, Jan-Olaf; Multhoff, Gabriele; Lüchtenborg, Anne-Marie (Frontiers in Oncology, 2023)
This is a provisional file, not the final typeset article water-filtered infrared A (wIRA) irradiation, immediately followed by hypofractionated re-irradiation with a total dose of 20-24 Gy, administered in weekly doses of 4 Gy. Tumor and tumor stroma biopsies as well as blood samples will be collected prior to treatment, during therapy (at a dose of 12 Gy) and in the follow-up to monitor therapy response. The treatment represents the standard operating procedure for hyperthermia plus re-irradiation. Various tissue and blood-based markers are analyzed. We aim at pinpointing key mechanisms and markers for therapy response which may help guiding treatment decisions in future. In addition, quality of life in the course of treatment will be assessed and survival data will be evaluated.Ethics: The study has been approved by the local ethics committee of the University of Freiburg, Germany (Ref 201 /19).Registration: The study is registered at the German Clinical Trials Register, Deutsches Register Klinischer Studien (DRKS00029221).